Wearing two hats: managing affiliation and instruction when responding to learner-initiated experiences in the adult ESL classroom. Issue 3 (2nd July 2020) - Hoi Yee Lo, Carol
ABSTRACT: Drawing on videotaped recordings from an Adult ESL class, this conversation-analytic paper examines how an experienced teacher responds to learner-initiated tellings of personal experiences while addressing the institutional goals of the language classroom. Specifically, I show three practices which enable the teacher to address institutional exigencies such as offering corrective feedback and restoring the progressivity of pedagogical activities without compromising the conveyance of affiliation. In so doing, the teacher can create rapport while fulfilling the pedagogic aims of the language classroom. Findings of this study shed light on how the interpersonal and the instructional dimensions of language teaching can be balanced in situ .